The girl before [compact disc, unabridged] : a novel - Delaney, JP (Random House Audio, 2017)
Seizing a unique opportunity to rent a one-of-a-kind house, a damaged young woman falls in love with the enigmatic architect who designed the residence, unaware that she is following in the footsteps of a doomed former tenant.